(untitled) (mathematica didactica, 2003)
Regarding the use of spreadsheet systems in mathematics instruction themathematics-didactical research was limited so far particularly to the investigation of case examples. Scientific research should go out however over an example collection, should abstract of special examples, show basic principles and answer general questions. An extension for a more general visibility on the topic arises from the fact that using spreadsheet systems is a special kind of programming. The article investigates this special kind of programming. Especially the relations are shown to the functional and to the imperative programming paradigm.